UMAT DAN KEWARGANEGARAAN (Suatu Tinjauan Konsep dan Hubungan antar keduanya) - Aminudin Aminudin (JURNAL SETIA PANCASILA, 2021)
This paper aims to reveal how the Islamic view regarding the concept of ummah and citizenship in on country concidering that at the beginning of the 20th century there has emerged what is called the concept of a nation-state so that Muslims are required to be able to respond as a historical fact. The study of term of ummah so far has been carried out by well-know scholars such Ali Shariati, he prefers the term ummah compared to the term qoum, qabilah, syu’ub, thaifah, congregation and others. Because the ummah has the aventage of having meaning content, which means dynamic humanity, not frozen an static entities. While the study of term citizenship mean membership which shows the relationship or bond between the state an citizens. Citizens as supporters of a state are the basis for the existence of a state, in other words that citizens are one of the important elements for a state in addition to other elements. And lastly the relationship between the two is the relationship the ummah and citizenship.